2022
DOI: 10.1097/med.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus and cognitive function: understanding the connections

Abstract: Purpose of reviewTo review the connection between type 2 diabetes and cognitive dysfunction, including its epidemiology, potential mechanisms of pathophysiology, risk factors, possible prevention, and treatment considerations.Recent findingsDiabetes is a risk factor for mild cognitive decline, in addition to Alzheimer's disease and vascular dementia. Duration of diabetes, concomitant vascular or associated co-morbidities, hyper- and hypoglycemia may lead to worsening cognitive dysfunction. Unfortunately, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 73 publications
0
8
0
6
Order By: Relevance
“…The results of the study will facilitate the development of personalized glycemic control strategies for patients with different conditions of T2DM, and hopefully improve the prevention strategies for different types of cognitive dysfunction related to diabetes. Many medical staff working on the clinical front line have observed that people with frequent hypoglycemic events seem to be more likely to develop cognitive impairment [42]. The association between hypoglycemia incidents and cognitive impairment in terms of doseresponse hasn't been explored, though.…”
Section: Plos Onementioning
confidence: 99%
“…The results of the study will facilitate the development of personalized glycemic control strategies for patients with different conditions of T2DM, and hopefully improve the prevention strategies for different types of cognitive dysfunction related to diabetes. Many medical staff working on the clinical front line have observed that people with frequent hypoglycemic events seem to be more likely to develop cognitive impairment [42]. The association between hypoglycemia incidents and cognitive impairment in terms of doseresponse hasn't been explored, though.…”
Section: Plos Onementioning
confidence: 99%
“…Diabetes is a risk factor for cognitive decline. Moreover, as the disease progresses, complications emerge, and blood glucose control deteriorates, the risk of developing cognitive impairment increases ( Dao et al, 2023 ; Sakib et al, 2023 ). Cognitive impairment, in turn, negatively impacts patients’ self-care and blood glucose management, fostering a vicious cycle ( Sinclair and Abdelhafiz, 2020 ).…”
Section: Evidence Of Cognitive Decline In Diabetes Patientsmentioning
confidence: 99%
“…Muscles and bones may get affected in severe cases to cause tissue necrosis and amputation. DF is thus the most serious complication of diabetes, and about 1/3 of diabetes patients possess infection risk [4]. Diabetes foot ulcer (DFU) may occur as the disease progresses [5].…”
Section: Introductionmentioning
confidence: 99%